Nilai-Nilai Didaktis dalam Cerpen Rubuhnya Sekolah Kami Karya A. BASKORO - Jasril Jasril; Asmawati (Yayasan Al-Afif, 2026)
This study aims to analyze the didactic values contained in the short story Rubuhnya Sekolah Kami by A. Baskoro. The study employs a descriptive qualitative approach using content analysis and a hermeneutic-didactic paradigm. The research data consist of words, sentences, and discourses that reflect didactic values. The findings show that the short story conveys didacticism through its plot, characterization, and setting. The didactic messages are presented logically through an understanding of students’ problems and their learning needs. The forms of didacticism are reflected in character education values such as creative thinking, honesty, and viewing nature as a source of learning inspiration. The use of everyday language makes Rubuhnya Sekolah Kami easy to understand and appropriate as teaching material for literature learning in schools.